Penambahan Fruktosa pada Semen terhadap Kualitas Motilitas dan Viabilitas Sperma Sapi Bali - Reski Amalia Burhanuddin; Musdalifa Mansur; Armayani M; Dhian Ramadhanty (Jurnal Galung Tropika, 2026)
This study aimed to analyze the effects of fructose administration and environmental conditions on the motility and viability of Bali cattle sperm. The study was conducted at the Artificial Insemination (AI) Service Unit over a two-month period, using an experimental method with a completely randomized design (CRD). Semen samples were collected from Bali bulls and then diluted using Andromed diluent at four different fructose concentrations: 0.1 ml, 0.3 ml, 0.4 ml, and 0.6 ml. Evaluations included analyses of sperm motility and viability before and after storage. The results showed no significant difference (p > 0.05) in sperm motility among the fructose treatments. The highest motility (70%) was recorded in the treatment with Andromed diluent + 0.4 ml of fructose; however, variations in fructose concentration did not significantly affect sperm motility. Furthermore, spermatozoa viability showed relatively similar results across all treatments, with the best viability observed at a 0.6 ml fructose concentration. Although fructose serves as an energy source for sperm, increasing the fructose concentration in the diluent did not significantly enhance motility. Environmental conditions such as temperature and humidity remain critical factors influencing sperm quality.